First Records of Erigorgus Species (Hymenoptera, Ichneumonidae, Anomaloninae) from Ukraine - Nuzhna, A.D. (Вестник зоологии, 2012)
Five species of the genus Erigorgus Förster: E. romani (Hellén), E. borealis (Hellén), E. femorator Aubert, E. villosus (Gravenhorst), E. lacertosus Atanasov are recorded from Ukraine for the first time. Previously unknown male of E. lacertosus Atanasov is described. E. villosus (Gravenhorst) is redescribed basing on additional characters not mentioned in original description. Приведены данные о 5 видах рода Erigorgus Forster: E. romani (Hellen), E. borealis (Hellen), E. femorator Aubert, E. villosus (Gravenhorst), E. lacertosus Atanasov, впервые обнаруженных в Украине. Для E. lacertosus Atanasov, описанного по самке, впервые приведено описание самца. E. villosus (Gravenhorst) переописан с использованием ряда признаков, не отмеченных в первоописании, но характерных для данного вида.